Acid-sensing ion channels mediate the degeneration of intervertebral disc via various pathways—A systematic review. Issue 1 (1st January 2019) - Guo, Yingjun; Meng, Yang; Liu, Hao; Wang, Beiyu; Ding, Chen; Rong, Xin; Yang, Yi; Hong, Ying
ABSTRACT: To elucidate the pathological significance of acid-sensing ion channels (ASICs) in intervertebral disc degeneration (IVDD), the database of Medline, Web of Science, and EmBase were carefully screened. Search terms used in each database varied slightly to optimize results. Data relating to the correlation between ASICs and IVDD was systematically collected and integrated into the review. 11 basic science studies, containing the related information, were finally identified for inclusion. Intervertebral disc degeneration (IVDD) is a common disease in middle-aged and elderly people, which has a great impact on patients' quality of life. Many research teams have attempted to elucidate the pathogenesis of this degenerative disease, and have made considerable progress. Acid-sensing ion channels (ASICs) were once reported to be able to regulate the apoptosis process of chondrocytes in joint cartilage, which has been transplanted into the IVDD-related research. ASIC1a functions as the mediator for cells in nucleus pulposus (NP) and endplate (EP), with whose activation the apoptosis process would be accelerated. Moreover, ASIC1a's activation could also regulate the anabolism in chondrocytes of EP, facilitating the degeneration. ASIC3 would only promote the degeneration in NP, possibly via its pro-inflammatory effect. The distribution of ASICs in NP, EP, annulus fibrosus, and the particular functions of ASIC1a and ASIC3 remind us about the pathological significance of ASICs in IVDD, which could be a promising therapeutic target in future treatment for IVDD.